EFFECTIVENESS OF EMPLOYEE PERFORMANCE AT THE REGIONAL WATER COMPANY (PDAM) TIRTA INDRAGIRI, INDRAGIRI HILIR REGENCY - Prayoga, Deny; ", Mayarni (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
This research is motivated by the presence of employee absenteeism problems, limited electricity supply, limited pipelines and limited pumps and distribution installation pipelines which have an impact on water supply that is not smooth and cannot meet customer needs in what is happening at the Regional Water Company (PDAM). Tirta Indragiri Hilir Tembilahan. The purpose of this study was to find out how the effectiveness of employee performance at the Regional Water Company (PDAM) Tirta Indragiri, Indragiri Hilir Regency, and to determine the factors inhibiting the effectiveness of its employee performance. This study used qualitative research methods. The selection of informants in this study used a purpose sampling technique. Collecting primary data from interviews, and secondary data from documentation and literature review. From the results of the research conducted, it can be concluded that the effectiveness of employee performance at the Regional Drinking Water Company (PDAM) Tirta Indragiri, Indragiri Hilir Regency when viewed from the two criteria used in measuring employee performance, namely Ability and Motivation, the results are still not optimal. Factors inhibiting the effectiveness of employee performance at the Regional Drinking Water Company (PDAM) Tirta Indragiri, Indragiri Hilir Regency, namely the low quality and quantity of human resources owned by the company, as well as limited facilities and infrastructure. Keywords: Performance, Employees, PDAM